1998
DOI: 10.1074/jbc.273.45.29786
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Endothelial Cell Monolayer Integrity Triggers Resynthesis of Vascular Endothelium Cadherin

Abstract: Although cadherins appear to be necessary for proper cell-cell contacts, the physiological role of VE-cadherin (vascular endothelium cadherin) in adult tissue has not been clearly determined. To shed some light on this question, we have disturbed the adhesive function of VE-cadherin in human endothelial cell culture using a polyclonal anti-VE-cadherin antibody. This antibody disrupts confluent endothelial cell monolayers in vitro and transiently generates numerous gaps at cell-cell junctions. The formation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
53
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 52 publications
(39 reference statements)
3
53
1
Order By: Relevance
“…In vivo, VE-cadherin endocytosis is one of the molecular mechanisms, by which VEGF induces endothelium permeability (Gavard and Gutkind, 2006). Disruption of endothelial contacts by the use of blocking antibodies against VE-cadherin induces endothelium permeability (Gulino et al, 1998) and rapid death (Corada et al, 1999). Further, the N-terminal domain of VE-cadherin is a potential target against tumor vascularization; it is transiently accessible during tumor angiogenesis and blocking with an antibody inhibits tumor growth (May et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In vivo, VE-cadherin endocytosis is one of the molecular mechanisms, by which VEGF induces endothelium permeability (Gavard and Gutkind, 2006). Disruption of endothelial contacts by the use of blocking antibodies against VE-cadherin induces endothelium permeability (Gulino et al, 1998) and rapid death (Corada et al, 1999). Further, the N-terminal domain of VE-cadherin is a potential target against tumor vascularization; it is transiently accessible during tumor angiogenesis and blocking with an antibody inhibits tumor growth (May et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, some of these have been shown to disrupt adherens junctions between cultured endothelial cells. 11 Other studies using three different antibodies (CAD5 directed against EC1, BV9 directed against EC3-4, and BV6 directed against EC3) showed that the three antibodies were highly active in several cellular assays, including permeability, calcium switch, and tube formation. These antibodies were also shown to inhibit the protective effect of VEGF on apoptosis.…”
Section: Ve-cadherin Antibodies In Autoimmune Disease L Bouillet Et Almentioning
confidence: 97%
“…4,5 Several antibodies blocking VE-cadherin have been described as potently interfering with the adhesive properties of the protein. 11,16 In several autoimmune diseases, autoantibodies to VE-cadherin (AAVEs) have been described; however, the target epitopes have yet to be identified. The present study was designed to examine whether AAVEs were present in serum from patients with autoimmune diseases.…”
Section: Ve-cadherin Antibodies In Autoimmune Disease L Bouillet Et Almentioning
confidence: 99%
See 2 more Smart Citations